Taboo Words Used By the Characters in Murder Mystery 2 Movie - Nurul Risci Aulia; Ni Ketut Widhiarcani Matra; Galuh Febri Putra (International Journal of Studies in International Education, 2024)
This analysis discussed the Taboo Words Used in Murder Mystery 2 Movie. The objectives of this study are to identify and describe the types and the functions of taboo words used in Murder Mystery 2 movie and to determine the most frequently used categories of the types and the functions of taboo words. Data were collected using note-taking and observation techniques. Mix method is used to categorize the types and functions of taboo words and determine their frequency. The results of discussion found seven types of taboo words with 175 occurrences taboo words. The most frequently used type is religious taboo (57.1%), predominantly involving the use of the word “god” with 82 occurrences, followed by scatological references and disgusting objects (21.1%), insulting references to perceived psychological, physical, and social deviations (11.4%), offensive slang (5.7%), sexual references (2.2%), animal names (1.7%), and ancestral allusions (0.5%). There are three functions of taboo words identified with 177 occurrences. The main function is to achieve personal outcomes (71.8%), primarily to intensify negative emotions, with 91 occurrences, followed by intensifying positive emotions and catharsis, each with 18 occurrences. Other functions include achieving interpersonal outcomes (17.5%), inconsequential outcomes (9.6%), and literal or denotative use (1.1%).